Application of Remote Sensing and GIS in Planning of Soil and Water Conservation Measures - Kumar, Hasmukh; Mittal, H K; Singh, R S; Purohit, R C; Singh, P K (Journal of Agricultural Engineering, 2007)
Development programmes for optimum utilization of natural resources are now increasingly planned on watershed basis. Proper planning and management of a watershed require detailed data viz. hydrologic behaviour of watershed, slope, rainfall pattern, land capability classification, land use etc., which govern the amount of runoff and soil loss produced by rainfall. Remote sensing and GIS techniques can be used successfully for the integration and analysis of above properties. In the present study remote sensing data are used for land information whereas GIS has been used for the integration of various thematic maps to delineate the areas suitable for adopting soil and water conservation measures. The major soil and water conservation measures proposed in Kalora-II micro-watershed of district Udaipur (Rajasthan) were contour bund, puerto rico terrace, stone wall terrace for arable land and contour trench, staggered trench, v-ditch, silvi-pasture development for non-arable land. A water harvesting structure of capacity 8.32 ha-m was also proposed for supplementary irrigation to rabi crops.